Changes in Brain-Health Related Modifiable Risk Factors in Older Adults After One Year of COVID-19-Restrictions - Waterink, Lisa; Bakker, Els D.; Visser, Leonie N. C.; Mangialasche, Francesca; Kivipelto, Miia; Deckers, Kay; Köhler, Sebastian; Sikkes, Sietske A. M.; Prins, Niels D.; Scheltens, Philip; Flier, Wiesje M. van der; Zwan, Marissa D. (Frontiers in Psychiatry, 2022)
Background The COVID-19 pandemic has major influence on lifestyle and mental health, which might affect brain-health and increase the risk of cognitive decline, particularly in older adults. We aimed to describe changes in modifiable risk factors related to brain-health in older adults after one year of COVID-19 restrictions. Methods An online survey was disseminated between February and March 2021 to 17773 registrants of the Dutch Brain Research Registry, aged ≥50, without a self-reported diagnosis of mild cognitive impairment or dementia. Participants were asked to report potential changes in behaviors during the COVID-19 pandemic, compared to pre-pandemic, in eight domains related to brain health: physical activity, sleep, feeling of memory decline, perceived stress, feeling of loneliness, diet, alcohol consumption and smoking. We used negative binomial regression analyses to relate (socio)demographics, subjective memory complaints and COVID-19 related aspects (fear of, or current/past COVID-19 infection) to the number of reported detrimental and beneficial changes as dependent variable. Results 3943 participants (66±8 years old; 76% female; 71% highly educated) completed the survey. After one year of COVID-19-restrictions, 74% reported at least one detrimental lifestyle change unfavorable for their brain health, most frequently reported were feelings of loneliness, sleep problems, and less physical activity. 60% of participants reported at least one beneficial change, which were most often more physical activity, healthier dietary habits, and less alcohol consumption. Individuals who are younger (incidence rate ratio (IRR) = 0.99, 95%CI = 0.98-0.99), female (1.20, 1.11-1.30), living alone (1.20, 1.11-1.28) and in urban environments (1.18, 1.08-1.29), who are less satisfied with their income (1.38, 1.17-1.62), experiencing subjective memory complaints (1.40, 1.28-1.52) and those with a past or current (1.19, 1.06-1.34) or fear of a COVID-19 infection (1.33, 1.25-1.42) reported higher numbers of detrimental changes. Discussion The COVID-19 pandemic has influenced lifestyle in both positive and negative ways. We identified (socio)demographic factors associated with more detrimental changes in modifiable risk factors related to brain health, suggesting that some individuals are more vulnerable for the impact of the COVID-19 pandemic. These findings provide an opportunity for targeted prevention and education to promote a healthy lifestyle during and after the pandemic.